The Examination Impact of Speculation and Profit Sharing to the Mudaraba Deposits in Indonesia Islamic Banks - Ruhadi Ruhadi; Setiawan Setiawan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This study aims to identify the motives of customers in investing their funds in Islamic banks in Indonesia. In general, there are two motives, speculation and investment, and these two motives want to be identified in this study. As is known from sharia business principles that speculation is prohibited while investment is a motive that is permissible and even highly recommended, so it is expected to have an impact on more productive activities and can provide maximum benefits at the opening of broader employment opportunities and increased welfare people. The data used in this study are financial reports from Islamic banks collected from OJK statistics, for the period 2013 to 2017. The analytical tool used in this study is multiple regression which will relate the dependent variable of mudaraba deposits as a representation of savings in Islamic banks with two independent variables consisting of stock prices to identify stock returns as a representation of the motive of speculation as well as profit sharing or ratio which is a representation of investment motives. The results showed that stock returns simultaneously did not influence the changes in mudaraba deposits. Nevertheless the results of the partial statistical analysis indicate that the RS has a negative and significant influence on mudaraba savings. The next finding is that profit and loss sharing has a positive and statistically significant simultaneous effect on mudaraba savings in Islamic banks.